Preoperative asymmetry is a risk factor for reoperation in involutional blepharoptosis. Issue 5 (May 2017) - Suga, Hirotaka; Ozaki, Mine; Narita, Keigo; Shiraishi, Tomohiro; Takushima, Akihiko; Harii, Kiyonori
Summary: Background: Patients with involutional blepharoptosis sometimes require reoperation because of functional or esthetic reasons after the primary operation. Few studies have analyzed the risk factors for reoperation in such cases. Methods: We retrospectively analyzed the cases of 274 patients who underwent levator aponeurosis surgery for bilateral involutional blepharoptosis. We examined the risk factors for reoperation using univariate and multivariate analyses. Results: Reoperation was performed for 89 of the 274 patients (32.5%). There was no significant difference in the rate of reoperation among surgeons. In the univariate analysis, patients with preoperative asymmetry, defined as a difference of >1 mm in the marginal reflex distance between the right and left sides, showed a significantly higher rate of reoperation (42.7%) than those without asymmetry (28.1%) ( p  = 0.018). Age, sex, and ptosis severity did not affect the rate of reoperation. The multivariate analysis with a logistic regression showed that preoperative asymmetry was a significant risk factor for reoperation, with an odds ratio of 1.90 ( p  = 0.019). Conclusion: In involutional blepharoptosis, patients with preoperative asymmetry should be informed of the higher risk of reoperation, and the balance between the right and left sides should be carefully adjusted intraoperatively.